Fitoquímica e atividade vasodilatadora "in vitro de" "Mansoa hirsuta D.C.". - Priscilla Rodrigues Valadares Campana (2008)
Mansoa hirsuta DC (Bignoniaceae) is a liana found in the Atlantic forest. There is no record of ethnomedical use for this species, although its leaves have been reported to inhibit in vitro the angiotensin-converting enzyme (ACE). The goal of the present study was to evaluate the potential antihypertensive effect of this species and to isolate the bioactive compounds. The vasodilator effect of the ethanolic extract of M. hirsuta leaves (EEF) was assayed in rat aortic rings. EEF produced a concentration-dependent vasodilatation (IC50 = 8.5 ± 0.6 ìg/mL), which was absent in endothelium-denuded vessels. The endothelium-dependent vasodilatation induced by EEF was abolished by LNAME (100Smol/L), a nitric oxide (NO) synthase inhibitor, but not by indomethacin (10 Smol/L; IC50 12.0 ± 0.8 Sg/mL), a cyclooxygenase inhibitor, suggesting a role for NO in the vasorelaxant response. The concentrationresponse curve of EEF was not modifiedby the addition of superoxide dismutase (SOD; 300 U/mL). In addition, theconcentrationresponse curve of 3-morpholinosydnonimine (SIN-1; IC50 = 2.75 ± 0.73 ìmol/L) was displaced to the left (p < 0.05) by EEF (50 ìg/mL; IC50 = 0.8 ± 0.11 ìmol/L) and by SOD (300 U/mL; IC50 = 0.67 ± 0.11 ìmol/L). These findings led us to conclude that EEF induces a NO- and endothelium-dependent vasodilatation in rat aortic preparations, and that this effect is, at least in some extent, due to an increase on theNO bioavailability as consequence of its antioxidant activity. EEF was submitted to fractionation by different chromatographic techniques (silica gel and Sephadex LH20 columns, RP-HPLC, HSCC) and/or partition between immiscible solvents, resulting in the isolation of three compounds, named PP1, PP2 and PP3. Mass spectra analysis of theseconstituents allowed their characterization as tetrameric proanthocyanidins, composed of two monomers of catechin and two units of afzelechin, or their corresponding epimers, along with a sugar residue. Identification of the flavan-3-ol units was confirmed for PP1 by mono and bidimensional 1H and 13C NMR experiments. This is the first report on the occurrence of proanthocyanidins in a Bignoniaceae species. The ACE inhibitory activity of the isolated compounds was assayed and only PP1 was active, producing 76 ± 2.7% of inhibition (100 ìg/mL). PP1 also produced a concentration- and NO-dependent vasorelaxant effect in aortic rings, with IC50 of 0.25 ± 0.1 Smol/L. These results corroborate the potential antihypertensive activity of M. hirsuta and disclose PP1 as one of active compounds of the species.